Epigrafía y literacy paleohispánica en territorio vascón: notas para un balance provisional (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this paper is to review the documents of Palaeohis- panic writing in the territory of ancient Vascones form the point of view of the writing systems used in the region.
Keywords: Palaeohispanic epigraphy; Vascones; Writing systems; Literacy